2013
DOI: 10.1155/2013/374925
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Microencapsulation of Human Islets Does Not Increase Susceptibility to Acute Hypoxia

Abstract: Islet transplantation in diabetes is hampered by the need of life-long immunosuppression. Encapsulation provides partial immunoprotection but could possibly limit oxygen supply, a factor that may enhance hypoxia-induced beta cell death in the early posttransplantation period. Here we tested susceptibility of alginate microencapsulated human islets to experimental hypoxia (0.1–0.3% O2 for 8 h, followed by reoxygenation) on viability and functional parameters. Hypoxia reduced viability as measured by MTT by 33.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
3
15
1
Order By: Relevance
“…Nevertheless, we showed that low oxygen tension significantly damages NPI function, metabolism and viability from 2 to 7 days of culture. In keeping with the literature describing the impact of ischemia or hypoxia on human pancreatic islets (Brandhorst et al, ; Cantley et al, ; Giuliani et al, ; Hals, Rokstad, Strand, Oberholzer & Grill, ; Lai et al, ; Moritz et al, ), our results suggest that the innovative oxygen supply strategy developed in the present study may also meet the challenges of hypoxia during allotransplantation of macroencapsulated human pancreatic islets.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, we showed that low oxygen tension significantly damages NPI function, metabolism and viability from 2 to 7 days of culture. In keeping with the literature describing the impact of ischemia or hypoxia on human pancreatic islets (Brandhorst et al, ; Cantley et al, ; Giuliani et al, ; Hals, Rokstad, Strand, Oberholzer & Grill, ; Lai et al, ; Moritz et al, ), our results suggest that the innovative oxygen supply strategy developed in the present study may also meet the challenges of hypoxia during allotransplantation of macroencapsulated human pancreatic islets.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, lack of vascularization and potential hypoxia is also an issue without capsules, however with capsules the potential ingrowth of blood vessels into the islets is physically hindered by the capsule. For short‐term (acute) hypoxia in vitro, no difference on viability or function was seen for encapsulated versus nonencapsulated human islets . However, culture of encapsulated islets under low oxygen conditions shows loss of viable tissue and necrotic cores .…”
Section: The Inner Life Of the Capsule—oxygen Supply And Microenvironmentioning
confidence: 96%
“…On the other hand, our recent experience with culture of human islets in capsules of similar size (450-500 µm) points towards a protective role of the alginate hydrogel for encapsulated tissue when cultured under limited oxygen supply [49].…”
Section: Alginate Matrices Do Not Stimulate Progenitor Maturation Intmentioning
confidence: 99%